Kajian terhadap Interpretasi Nicolai Sinai dalam An Interpretation of Sura>h al-Najm (QS.53) - Ulya, Nurun Najmatul (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2020)
AbstractThe article discusses the interpretation of Surat al-Najm Nicolai Sinai by using the literature review method. The article aims to explain the background of the interpretation, the methods used, to the form of interpretation produced by Nicolai Sinai. As a way to find out the characteristics of the interpretation of Surah al-Najm Sinai compared to the interpretations of other exegete, the article also examines the interpretations made by other exegete on Surah al-Najm, both classical and contemporary. The study concludes that the background to Nicolai Sinai's interpretation of surah al-Najm is to voice his opinion on the debates of scholars about the verse ghara>ni>q and to discuss in more detail the verses that explain the encounter of the Prophet Muhammad with Allah. The following are Sinai's conclusions about Surah al-Najm that differ from the interpretation produced by exegetes. 1) the 7th verse of Surah al-Najm clearly says that the Prophet Muhammad met with Allah; 2) verses 23 and 26 to 32 are parenthetical paragraphs for the structure and content are not following the unity of the verse; 3) Satan verses or ghara>ni>q verses are not part of revelation. The Sinai's study was published in the Journal of Qur'anic Studies in 2011 with the title An Interpretation of Surah al-Najm (QS.53). AbstrakTulisan ini membahas interpretasi surat al-Najm Nicolai Sinai dengan menggunakan metode kajian pustaka. Tujuan kajian ini adalah hendak memaparkan latar belakang interpretasi, metode yang digunakan, hingga bentuk interpretasi yang dihasilkan oleh Nicolai Sinai. Tulisan ini juga mengkaji penafsiran yang dilakukan oleh mufassir lain terhadap surat al-Najm, baik klasik maupun kontemporer untuk mengetahui ciri khas interpretasi surat al-Najm Sinai dengan para mufassir lain. Kajian ini mendapatkan kesimpulan bahwa latar belakang interpretasi Nicolai Sinai terhadap surat al-Najm adalah untuk menyuarakan pendapatnya terhadap perdebatan para sarjanawan tentang ayat ghara>ni>q dan untuk membahas lebih detail ayat yang menjelaskan tentang berjumpanya Nabi Muhammad dengan Tuhan. Kesimpulan Sinai terhadap surat al-Najm yang berbeda dari penafsiran yang selama ini dilakukan oleh mufassir adalah: 1) ayat ke-7 surat al-Najm jelas mengatakan bahwa Nabi Muhammad bertemu dengan Tuhan, Sang Penutur Wahyu; 2) Ayat k3 23 dan 26 hingga 32 merupakan ayat sisipan karena secara struktur dan konten tidak sesuai dengan kesatuan surat; 3) Ayat setan atau ayat ghara>ni>q bukan bagian dari wahyu. Kajian Sinai ini dimuat dalam Journal of Qur’anic Studies pada tahun 2011 dengan judul An Interpretation ofSura>h al-Najm (QS.53).Kata Kunci: Interpretasi, Surat al-Najm, Nicolai Sinai